2020
DOI: 10.3390/pathogens9070519
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease Pandemic (COVID-19): Challenges and a Global Perspective

Abstract: The technology-driven world of the 21st century is currently confronted with a major threat to humankind, represented by the coronavirus disease (COVID-19) pandemic, caused by the severe acute respiratory syndrome, coronavirus-2 (SARS-CoV-2). As of now, COVID-19 has affected more than 6 million confirmed cases and took 0.39 million human lives. SARS-CoV-2 spreads much faster than its two ancestors, SARS-CoV and Middle East respiratory syndrome-CoV (MERS-CoV), but has low fatality rates. Our analyses sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 140 publications
(176 reference statements)
0
65
0
4
Order By: Relevance
“…The available data do show no increased or even lower maternal mortality rate after infection [25], but it does not mean that pregnancy is a protective factor for severe infection. It was reported that severe infection mostly occurred in the elderly (> 60 years old), patients with basic diseases, such as diabetes, obesity, hypertension, coronary heart disease, cerebrovascular diseases, and other chronic diseases [26][27][28][29][30], as well as those who did not receive timely treatment or delay treatment [31]. Pregnant women are usually younger without primary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The available data do show no increased or even lower maternal mortality rate after infection [25], but it does not mean that pregnancy is a protective factor for severe infection. It was reported that severe infection mostly occurred in the elderly (> 60 years old), patients with basic diseases, such as diabetes, obesity, hypertension, coronary heart disease, cerebrovascular diseases, and other chronic diseases [26][27][28][29][30], as well as those who did not receive timely treatment or delay treatment [31]. Pregnant women are usually younger without primary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in the journal Cell showed that the RBD dimer design has the ability to generate a higher specific IgG response with a much more elevated NAb titer by up to 10–100-folds than a conventional RBD monomer vaccine, based on studies conducted on mice models ( 91 ). Another benefit to the RBD dimer design is that it has the ability to be manufactured on a large-scale which is ideal for a pandemic situation like COVID-19 ( 90 ). Although this novel approach is still very much at the early stage of development it will be interesting to closely monitor progress in the development of this vaccine platform.…”
Section: Future Outlook and Concluding Thoughtsmentioning
confidence: 99%
“…Few countries are left beyond the reach of this unfortunate pandemic. However, their possibility of remaining untouched by this virus is meagre because, within a short period, the virus emerged in many new countries, including India, where the statistics are uprising [68]. Now the number of confirmed cases and deaths is shooting day by day with no hope of sudden halt, leaving the global population in a stage of physiological, psychological, and socioeconomic stress.…”
Section: Sars-cov-2mentioning
confidence: 99%